De-constructing risk, therapeutic needs and the dangerous personality disordered subject - O'Loughlin, Ailbhe (Punishment & society, 2019)
The focus of this article is on the Dangerous and Severe Personality Disorder Programme and its successor, the Offender Personality Disorder Pathway: two initiatives in England and Wales with the aim of protecting the public from dangerous offenders through a combination of preventive detention and therapeutic intervention in prisons and psychiatric hospitals. In this article, I first explore how the dangerous yet potentially redeemable dangerous and severe personality disordered subject was constructed by policymakers before turning to examine how the risks this group posed were translated into therapeutic needs under the Dangerous and Severe Personality Disorder Programme. In so doing, I contend that prisoners’ mental health needs are not only targeted for humane reasons but also as a means of facilitating the cost-effective management of difficult and disruptive individuals. Furthermore, meeting these needs can serve as an intermediate step towards drawing difficult prisoners into mainstream offending behaviour programmes explicitly targeting criminogenic risk factors. Ultimately, I conclude that, given that meeting prisoners’ mental health needs is contingent on the compatibility of therapeutic regimes with the priorities of the prison, treatment programmes will ultimately yield to the overriding concerns of security and control in the event of conflict.